Bilder i bruk Samuli Paulaharjus fotografier i dokumentasjonens og illustrasjonens tjeneste - Aarekol, Lena; Ryymin, Teemu (Landslaget for lokalhistorie, 2006)
This article is part of Lena Aarekol's doctoral thesis. Available in Munin at http://hdl.handle.net/10037/2596 Since the late 1970s, Norwegian historians have debated the standing of photographs in historical research. Efforts have been made to establish photographs as sources, not merely illustrations in historical narratives. The present article discusses the use of photographs taken in Northern Norway in the 1920s and 1930s by the Finnish author Samuli Paulaharju, best known for his research on Finnish folk culture. Paulaharju’s photographs have been, and still are, used to tell many different stories. While Paulaharju himself used these photographs in his books to illustrate Finnish culture and history as it manifested itself among the Finnish-speaking minority on the shores of Arctic Ocean, in Norway his photographs have been used to illustrate and partly also document Northern Norwegian cultural and social history and Kven history. The analysis also shows that the photographs are widely used in a positivistic manner: they are seen as representing historical reality, whereas in practice the meaning ascribed to the photographs is contingent on the context of their deployment. In a consequence, we argue that the position of photographs as a source must be reinforced, and that the usual rules of source criticism must also be applied to photographs.